Serum visfatin level in prediabetics and its relation to left ventricular function - Mohammed Abdel-Hassib (The Egyptian Journal of Internal Medicine, 2019)
Introduction Visfatin is a molecule of clinical relevance, released mainly from visceral fat (hence it named as such) and could be a promising biomarker with diagnostic and prognostic significance in metabolic syndrome. Very little is known about visfatin and its relation with prediabetes. Objective The present study was conducted to demonstrate the relationship between serum visfatin level and prediabetes and its relation to left ventricular function. Patients and methods We studied 60 prediabetic patients recently diagnosed according to ADA criteria 2014 and classified into two groups according to the BMI. They were compared with 30 healthy matched controls. All groups underwent complete history taking, general examination, laboratory investigations (including homeostasis model assessment-insulin resistance and serum visfatin level), and two-dimensional transthoracic echo Doppler study at baseline and 8 months thereafter only for the patient groups. Results This study showed that there is a positive correlation between serum visfatin level and prediabetes and left ventricular function. Conclusion Serum visfatin is an early and strong predictor of prediabetes and left ventricular dysfunction.